Lower gut abundance of Eubacterium rectale is linked to COVID-19 mortality - Liu, Yingzhi; Chan, Matthew T. V.; Chan, Francis K. L.; Wu, William K. K.; Ng, Siew C.; Zhang, Lin (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Emerging preclinical and clinical studies suggest that altered gut microbiome composition and functions are associated with coronavirus 2019 (COVID- 19) severity and its long-term complications. We hypothesize that COVID-19 outcome is associated with gut microbiome status in population-based settings. Methods Gut metagenomic data of the adult population consisting of 2871 subjects from 16 countries were obtained from ExperimentHub through R, while the dynamic death data of COVID-19 patients between January 22, 2020 and December 8, 2020 in each country was acquired from Johns Hopkins Coronavirus Resource Center. An adjusted stable mortality rate (SMR) was used to represent these countries’ mortality and correlated with the mean relative abundance (mRA) of healthy adult gut microbiome species. Results After excluding bacterial species with low prevalence (prevalence <0.2 in the included countries), the β-diversity was significantly higher in the countries with high SMR when compared with those with median or low SMR (p <0.001). We then identified the mRA of two butyrate producers, Eubacterium rectale and Roseburia intestinalis, that were negatively correlated with SMR during the study period. And the reduction of these species was associated with severer COVID-19 manifestation. Conclusion Population-based microbiome signatures with the stable mortality rate of COVID-19 in different countries suggest that altered gut microbiome composition and functions are associated with mortality of COVID-19.